Rancangan Media Pembelajaran Berbasis Augmented Reality (AR) pada Mata Pelajaran Tik Kelas X di SMA Negeri 1 Ciruas - Lola Lorenza; Dewi Surani; Ade Fricticarani (Departement of Mathematics Education, 2024)
The research objective of this research is to create a design for learning media based on Augmented Reality (AR) to make it easier for students to learn subjects, as well as to determine the feasibility, practicality and effectiveness of learning media based on Augmented Reality (AR). This research is Research and Development (R&D) research. The trial was carried out on 36 class X students of SMA Negeri 1 Ciruas. This research method uses the (ADD) Analysis, Design, Development model, which is a development model used to design learning products which are then systematically tested in the field, in the form of needs analysis and to test the effectiveness of the product so that it can function in the wider community, research is needed to test the effectiveness of the product. The assessment from 3 validators of Augmented Reality (AR) Based Learning Media, namely 82%, shows that Augmented Reality (AR) Based Learning Media is valid to use as a learning resource. Augmented Reality (AR) Based Learning Media. Student and validator responses show that Augmented Reality (AR) Based Learning Media is very good to use as a learning resource.